Concepções de Guerra Fria nos quadrinhos : as narrativas gráficas dos super-heróis no século XX : do Capitão América a Watchmen - Sanches, Rogério Luís Gabilan (2021)
This thesis investigates the conceptions of the Cold War (1947-1989) and their representations in comic books. The elaboration of the narrative present in these cultural artifacts is one of the main points to be addressed in this investigation. After the end of World War II (1939-1945), with the defeat of Nazi-fascism in Europe, the rise of the two victorious military-political superpowers took place, the United States of America, leader of the capitalist bloc and; the Soviet Union, from the socialist. The construction, by the US media and politics, of a new “total enemy” also began: “communism” or “red threat”. The Cold War was inaugurated. In this scenario of geopolitical bipolarity, we will analyze three characters from the Marvel Comics publisher: the Second World War hero Captain America, who resurfaced in the 1950s, during McCarthyism or the Witch Hunt; Iron Man and Fantastic Four, also important for the propagation of anti-communist ideology, especially during the arms and space races of the 1960s. The politics of US President Ronald Reagan during the 1980s, in turn, will be seen in the pages of the Graphic Novels of DC Comics Batman - The Dark Knight Returns and Watchmen. We will proceed with the analysis not only of the discourses used in these narratives, but also of image fragments present in these works. We understand that the approach of non-verbal elements such as colors, shadows and posture of these characters is as important as the verbal and written analysis contained in these comics. Nevertheless, the substantive concept of the Cold War will be approached through the controversy present in contemporary historiography. Anti-communist propaganda is of paramount importance for the purposes of this investigation, since it is a historiographical interpretation. Comics are not innocent. They serve political interests and circumstances. From the color of superhero uniforms to the superiority discourse, these cultural artifacts will be discussed not only from a narrative and imagery point of view, but also from a historiographical perspective.